Measuring the Paid Off-Farmwork Contributions of Women in Australian Agricultural and Rural Communities - Jefferson, Therese; Mahendran, Anusha (World Business Institute Australia, 2012)
The invaluable social and economic contribution that women collectively make is often undervalued and underestimated. This paper attempts to address this to some extent, by providing a contemporary assessment of women’s contribution to paidoff farm work in rural and agricultural communities in Australia. As part of the analysis, women’s contributions to paidoff farm work activities are examined. Measures of the contribution of women in terms of their contribution to paidoff farm work are calculated using values derived from specially constructed models. A brief literature review of relevant research concerning the determinants of women’s contribution to paid off farm work in the agricultural and rural communities is also incorporated. The findings presented are thus largely based on current research, with one of the main goals of the exercise being to provide more complete information regarding the contribution of women to agricultural and rural communities, to improve future policy development and implementation in relevant areas.